IMPLEMENTATION OF THE EXCLUSIVE BREASTFEEDING PROGRAM TO PREVENT STUNTING IN INFANTS AT PUSKESMAS KEDUNG JAYA VILLAGE - M. Anissul Fata; Winda Dwi Yanthi; Gian Fitralisma; Rohmatul Fawaiz; Maulipah Maulipah; Sundari Sundari (Jurnal Abdisci, 2025)
Abstract Background: Exclusive breastfeeding is an important effort in preventing infant stunting. Aims: This study aims to analyze the implementation of the exclusive breastfeeding program at the Kedung Jaya Village Health Center and identify the supporting factors and obstacles faced. Methods: The research method was descriptive qualitative with a case study approach. Data were obtained through interviews with health workers, observation of counseling activities, and questionnaires to breastfeeding mothers. Result: The results showed that the exclusive breastfeeding program has been running well, marked by mothers' increasing awareness of its importance. The main factors supporting its success are routine counseling, individual lactation counseling, and the active role of posyandu cadres. However, some challenges remain, such as cultural influences that assume infants need additional food before 6 months and limited time for working mothers to provide exclusive breastfeeding. Implementation: Based on these findings, more personalized and community-based education strategies, provision of lactation facilities for working mothers, and further training for posyandu cadres are needed. With improvements in the implementation of this program, exclusive breastfeeding rates can increase, and the prevalence of stunting in Kedung Jaya Village can decrease significantly.